INSIGHT ON THYMOSIN BETA 4 IN ANIMAL MODELS OF MYOCARDIAL INJURY - Stark, Christoffer (fi=Turun yliopisto|en=University of Turku|, 2017)
The use of small and large animal models is vital in the clinical translation of experimental data in cardiovascular research. Thymosin beta 4 is a peptide which has shown good cardioprotective potential in several in vitro and animal experiments. The peptide increases cell survival, angiogenesis and progenitor cell migration while it reduces inflammation and cell death. In small animal models for myocardial infarction it limits infarct size and improves cardiac function. It has also shown promising effect in pig models for myocardial injury. In this thesis, we aimed to determine the effect of the peptide in mouse models for myocardial infarction and anthracycline-induced cardiomyopathy and in a pig model for global ischemia-reperfusion injury. We focused on improvement in cardiac functional outcome by performing echocardiography, magnetic resonance and positron emission tomography imaging. The underlying mechanism were investigated by measuring cell death, inflammation and gene-expression analysis. After myocardial infarction thymosin beta 4 treatment may have reduced infarct expansion and left ventricle remodeling with improvement in left ventricle function. Treatment was associated with upregulation of chitinase 3-like-1, a novel protein involved in fibrosis and inflammation. We also observed increased activity of the cardioprotective enzyme CD73. Anthracycline caused high mortality with limited change in cardiac contractility and was therefore not considered suitable for inducing experimental cardiac dysfunction. Thymosin beta 4 did not attenuate global myocardial ischemia-reperfusion injury nor did it influence myocardial cell death or inflammation. The cardioprotective effect seen in mice could not be demonstrated in pigs and further therapeutic evaluation is therefore needed.

Små och stora försöksdjursmodeller är viktiga för att utveckla prekliniska resultat inom kardiovaskulär forskning. Thymosin beta 4 är en peptid som visat kardioprotektiva egenskaper i flera in vitro och försöksdjursexperiment. Peptiden förbättrar cellernas överlevnad efter olika typer av stress, hämmar inflammation och ökar utvecklandet av nya blodkärl. Efter behandling för hjärtinfarkt minskar peptiden i små försöksdjursmodeller infarktstorleken och leder till förbättrad hjärtfunktion. Den har också visat lovande resultat i grismodeller för hjärtmuskelskada. I den här avhandlingens delarbeten undersöktes peptidens effekter efter hjärtinfarkt och antracyklin-inducerad hjärtsvikt med hjälp av musmodeller och efter iskemi-reperfusionsskada på hjärtat i en grismodell. Vi utförde avbildningsundersökningar för att bestämma peptidens inverkan på hjärtats funktion efter hjärtskadorna och undersökte också mängden av hjärtcellsdöd, inflammation och förändringar i hjärtats genekspression. Thymosin beta 4 behandlingen förbättrade möjligtvis hjärtfunktionen och minskade infarktområdets utvidgning och hjärtats remodellering. Chitinase 3-like-1, ett protein som påverkar inflammation och produktionen av bindvävnad upreglerades efter behandlingen. Aktiviteten av det kardioprotektiva entsymet CD73 var också förhöjt. Dödligheten hos antracyklinbehandlade möss var hög och hjärtfunktionen var inte märkbart nedsatt. Därför ansågs behandlingen inte vara lämplig för att orsaka hjärtsvikt. Thymosin beta 4 hade ingen inverkan på hjärtat efter iskemi-reperfusionskada. Behandlingen minskade inte heller mängden av celldöd eller inflammation. Den kardioprotektiva effekten hos möss kunde därmed inte påvisas i grismodellen och ytterligare terapeutisk utvärdering av peptiden är nödvändig i framtiden.